Implementasi Ekowisata PT. Wakatobi Dive Resort dalam Upaya Konservasi Maritim di Pulau Tomia Kabupaten Wakatobi - Tarani, Sasti Putri; Rosnani, Rosnani (Universitas Bosowa, 2025)
PT. Wakatobi Dive Resort is a tourism business that, since 1996, has built an ecotourism-based marine tourism business. This research aims to determine the implementation of ecotourism by PT. Wakatobi Dive Resort in maritime conservation efforts on Tomia Island, Wakatobi Regency. The Wakatobi Coral Reef Conservation Collaboration Program (Wakatobi Coral Reef Conservation Collaboration Program) is one of the ecotourism program implementations carried out by PT. Wakatobi Dive Resort for maritime conservation purposes by involving local communities. In this research, the author used qualitative methods in conducting research, data collection techniques were taken from various sources, which included observation, oral and written interviews and library research. The Wakatobi Collaborative Coral Reef Conservation Program has 14 practices that impact the environmental, sociocultural, and economic aspects of Tomia Wakatobi Island. These environmental, sociocultural, and economic aspects are a form of ecotourism and maritime conservation. The Wakatobi Coral Reef Collaboration Program has built reciprocal relationships between the resort and the community. The creation of a better conservation area through collaboration between PT. Wakatobi Dive Resort, the National Park Office, and other coral reef patrols. The Wakatobi Coral Reef Collaboration Program preserves marine biodiversity and dozens of marine tourism destination spots in conservation areas.